Identification of Largemouth Bass Virus in the Introduced Northern Snakehead Inhabiting the Chesapeake Bay Watershed. Issue 3 (29th July 2013) - Iwanowicz, L.; Densmore, C.; Hahn, C.; McAllister, P.; Odenkirk, J.
Abstract: The Northern Snakehead Channa argus is an introduced species that now inhabits the Chesapeake Bay. During a preliminary survey for introduced pathogens possibly harbored by these fish in Virginia waters, a filterable agent was isolated from five specimens that produced cytopathic effects in BF‐2 cells. Based on PCR amplification and partial sequencing of the major capsid protein (MCP), DNA polymerase (DNApol), and DNA methyltransferase (Mtase) genes, the isolates were identified as Largemouth Bass virus (LMBV). Nucleotide sequences of the MCP (492 bp) and DNApol (419 pb) genes were 100% identical to those of LMBV. The nucleotide sequence of the Mtase (206 bp) gene was 99.5% identical to that of LMBV, and the single nucleotide substitution did not lead to a predicted amino acid coding change. This is the first report of LMBV from the Northern Snakehead, and provides evidence that noncentrarchid fishes may be susceptible to this virus. Received April 8, 2013; accepted April 19, 2013